The Impact of ICT-based Learning Tools on ESL Learners: A Study on the Role of ICT in Developing Communicative Competence in English Language: Exploring the Impact of ICT on English Language Learning (Journal of Advances and Scholarly Researches in Allied Education, 2017)
ICT (Information and Communication Technology) has influenced every walk of our life in modern times. Education cannot remain unaffected by the influence of ICT today. In this era of smartphones and handheld computing devices, there have been significant studies regarding the impact of ICT on English language learning. These studies have shown that the use of ICT tools and mobile assisted learning Apps can generate immense possibilities for the learners of a foreign language like English to develop their language skills (Chang Hsu, 2011). Many such apps are currently available for learning English as a Second Language (ESL) which have proved to be strong pedagogical tools that can be used by teachers to generate interest and passion for learning the language. This study is pertaining to the opinion of the respondents regarding the development of communicative competence in English language by using ICT. Questionnaires were administered to 20 ESL students studying various undergraduate courses in various colleges of Karnataka State. These students were familiar with the use of ICT tools and hence they were asked to express their views on a) ICT devices owned by them b) usage pattern of ICT and c) opinion regarding the impact of ICT on communicative competence. The outcome of the study indicated a positive attitude of the respondents towards the integration of technology to improve the quality of learning.